2016
DOI: 10.1111/sms.12725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute static, ballistic, and PNF stretching exercise on the muscle and tendon tissue properties

Abstract: The purpose of this study was to investigate the influence of a single static, ballistic, or proprioceptive neuromuscular facilitation (PNF) stretching exercise on the various muscle‐tendon parameters of the lower leg and to detect possible differences in the effects between the methods. Volunteers (n = 122) were randomly divided into static, ballistic, and PNF stretching groups and a control group. Before and after the 4 × 30 s stretching intervention, we determined the maximum dorsiflexion range of motion (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
132
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(157 citation statements)
references
References 36 publications
18
132
3
4
Order By: Relevance
“…PRT was not changed at any time point after the single static stretching exercise. This is in accordance with some other studies (Magnusson, Aagard, Simonsen, & Bojsen-Møller 1998), but not all the previous studies dealing with similar (Kay et al, 2015;Opplert et al, 2016) or higher durations of stretching (Kay & Blazevich, 2009;Konrad et al, 2017a;2017b;2019;Konrad & Tilp, 2020;Nakamura, Ikezoe, Takeno, & Ichihashi, 2013;Opplert et al, 2016). The controversial results of Kay et al (2015), who also considered 1 min of total stretching, might be explained by the different stretching approaches.…”
Section: Statistical Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…PRT was not changed at any time point after the single static stretching exercise. This is in accordance with some other studies (Magnusson, Aagard, Simonsen, & Bojsen-Møller 1998), but not all the previous studies dealing with similar (Kay et al, 2015;Opplert et al, 2016) or higher durations of stretching (Kay & Blazevich, 2009;Konrad et al, 2017a;2017b;2019;Konrad & Tilp, 2020;Nakamura, Ikezoe, Takeno, & Ichihashi, 2013;Opplert et al, 2016). The controversial results of Kay et al (2015), who also considered 1 min of total stretching, might be explained by the different stretching approaches.…”
Section: Statistical Analysessupporting
confidence: 91%
“…Kay, Husbands-Beasley and Blazevich (2015) reported decreased muscle stiffness (and no changes in tendon stiffness) following 4 × 15 s of static stretching, which could ex-plain the decrease in peak moment reported in Kay and Blazevich (2008). Decreased muscle stiffness following a single static stretching exercise has also been reported (Kay & Blazevich, 2009;Konrad, Budini, & Tilp, 2017a;Konrad, Stafilidis, & Tilp, 2017b), but not by all authors (Kato, Kanehisa, Fukunaga, & Kawakami, 2010;Kubo, Kanehisa, Kawakami, & Fukunaga, 2001) who tried to find the mechanism behind the increase in RoM and a possible decrease in performance. Far fewer studies are available that analyzed the time course of the changes of different parameters of the muscletendon function and structure following the stretching.…”
Section: Introductionmentioning
confidence: 83%
“…Many clinicians such as physicians and athletic trainers use stretching to prevent muscle cramps; some believe it is very effective . Two of the most common types of stretching include static stretching and proprioceptive neuromuscular facilitation (PNF) . Static stretching involves placing a muscle in a lengthened position, usually at the point of discomfort, and then holding that position for a period of time.…”
mentioning
confidence: 99%
“…18,19 Two of the most common types of stretching include static stretching and proprioceptive neuromuscular facilitation (PNF). 20 Static stretching involves placing a muscle in a lengthened position, usually at the point of discomfort, and then holding that position for a period of time. PNF stretching techniques vary although most utilize combinations of rest, contraction of target or antagonist muscles, and static stretching.…”
mentioning
confidence: 99%
“…In recent years, the effects of static stretching on muscle, tendon, and joint flexibility have been studied. These studies have shown that, although static stretching improves muscle and joint flexibility, it is unlikely to lead to acute or chronic improvement in tendon (structure) stiffness. In other words, while static stretching, which is currently widely used, improves muscle and joint flexibility, it does not improve tendon flexibility.…”
Section: Discussionmentioning
confidence: 99%